ANALISIS INFORMASI AKUNTANSI TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pasaribu, Heni Renata Br Pasaribu Heni Renata; Purba, Mortigor Afrizal (LPPM Universitas Putera Batam, 2021)
The stock price reflects the company's performance. The better the company, the higher the stock price. Therefore companies need to improve the company so that prices must increase. One way to study companies that have a company with a comparison compared to financial companies in the next year ahead. This study aims to increase the ratio of current, return on equity and net profit margin to the stock prices of pharmaceutical companies on the Indonesia Stock Exchange in 2015-2019 . The population in this study was the trial of 10 Pharmaceutical companies with the period 2015-2019. While the sample chosen by purposive sampling method with the number of 5 companies for 6 years processed data as much as 30 data. Data tested using basic assumptions, classic assumption tests, multiple linear regression tests and hypothesis testing. Current, Return On Equity and Net Profit Margin ratios have a significant effect on stock prices, this is seen from the significance value of the F test of 0,000 <0,05. The current and positive ratio is not significant to stock prices, can be seen from the significance value of 0.462> 0.05. Equity Returns. Can be seen from the significance value of 0.001 0.05.